Penggunaan Serat Kelapa untuk Pengolahan Limbah Cair Domestik - Hajimi Hajimi; Salbiah Salbiah; Susilawati Susilawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
The oil and fat content in domestic wastewater is an element that can cause pollution of water bodies and inhibits the continued process in the Waste Water Treatment Plant. For this reason, efforts should be made to eliminate the womb in wastewater by filtration. In this study the filtration process uses a laboratory scale that is making a waste water solution from a mixture of water with various types of cooking spices that are fried using cooking oil and butter. The purpose of the study was to analyze the effectiveness of coconut fiber as a filter for waste oil (fat) in domestic wastewater. The research starts from the process of making coconut fiber and filtration tanks until it continues to the filtration treatment process. The results showed there were significant differences in oil (fat) levels in domestic wastewater between before and after filtration using coconut coir fiber media with a thickness of 20 cm, 40 cm and 60 cm, which obtained the value of p (p-value) ≤ value α (0 , 05), i.e. 0.019, 0.02 and 0.006. There is no significant difference in effectiveness between variations in thickness of coconut coir fibers as a filtration media against decreasing levels of oil (fat) in domestic wastewater, where a p-value of 0.073> α (0.05) is obtained. The effectiveness of each reduction is 89.24 (thickness 20 cm), 0.02 (thickness 40 cm) and 0.006 (thickness 60 cm). Coconut fiber is effective as a filtration media for treating domestic wastewater that contains oil (fat). It is recommended to conduct further research by increasing the residence time of wastewater in the filtration bath.